PROCESS AND SYSTEMS Predictors of 30-day hospital readmission: The direct comparison of number of discharge medications to the HOSPITAL score and LACE index. Issue 3 (2019) - Robinson, Robert; Bhattarai, Mukul; Hudali, Tamer; Vogler, Carrie
No abstract available